Adult education, Islam, and socio-economic development (2017)
Seeking education knows no bounds, age, gender and race in the ancient and modem world. In Islam, the first act (Q2:31-33) and Quranic revelation about 1437 years ago was on education and knowledge acquisition (Q96:l-5). Education is undeniably important and cannot be overemphasized in all the affairs of man, whether social, political, economic and spiritual. This paper, therefore, examines the concept, importance and role of adult education in general and Islamic perspective of adult education in particular relating these to socio-political and economic development. This is done with a view to hypothesizing that education, whether for adults or youths, dictates the level of social and economic development because one cannot give what one does not have. Thus, education can have no ending because it is life. Being a qualitative study, the researchers utilize descriptive methodology to analyze data on adult education to support the paper’s arguments. Findings reveal that Islam provides solutions educationally to resource constraints (human and material) which are the major determinants of the sustainability of social and economic development, the abandonment of which culminated in underdevelopment, crass illiteracy, poverty, ignorance and discouragement of scientific enquiry. The paper analyzed many Quranic verses that encourage man (as homo sapiens) to think, ponder, reflect and discover improved ways of socio-political and economic life for sustainable development (e.g. Q27:69 and Q29:20). The paper recommends properly targeted and delivered adult education to end social strife in today’s world.